A Green's function solution to the transient heat transfer through the building wall. (28th March 2016) - Zhu, Zhongwei; Fan, Hongming; Hua, Jing; Zhang, Cheng
A Green's function method is proposed to calculate transient heat flow through the building wall in this article. In order to obtain a simplified analytical solution for dynamic heat transfer problems, approximation is applied to the solution. And it can also make numerical simulation faster. The approximation solution and the exact solution got by MATLAB are compared under four different heat transfer conditions for a practical problem to verify its accuracy. Furthermore, double layer building wall analysis model is developed for practical application.